2020
DOI: 10.1096/fj.201900393rr
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide protects against particle‐induced inflammatory response and osteolysis via SIRT1 pathway in prosthesis loosening

Abstract: Wear debris‐induced osteolysis and ensuing aseptic loosening is the main cause of implant failure and revision surgery. Wear debris‐induced inflammatory response plays key roles in peri‐implant osteolysis. Recently, substantial of evidence suggests that hydrogen sulfide (H2S), the third gasotransmitter, is a critical player regulating inflammation. However, the role and therapeutic potential of H2S in wear debris‐induced inflammation and osteolysis remains to be defined. In the present study, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…SIRT1 might be involved in the mechanisms by which astaxanthin modulates Nrf2/Prx2/ASK1/p38 signalling after traumatic brain injury. SIRT1 is a type of histone deacetylase that regulates a variety of cellular biochemical processes (Li et al, 2020; Liu et al, 2020; Wu et al, 2018; Zhang, Bi, et al, 2019). Mounting evidence indicated that SIRT1 could enhance the expression and transcriptional activity of Nrf2 to exert potent anti‐oxidant effects (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 might be involved in the mechanisms by which astaxanthin modulates Nrf2/Prx2/ASK1/p38 signalling after traumatic brain injury. SIRT1 is a type of histone deacetylase that regulates a variety of cellular biochemical processes (Li et al, 2020; Liu et al, 2020; Wu et al, 2018; Zhang, Bi, et al, 2019). Mounting evidence indicated that SIRT1 could enhance the expression and transcriptional activity of Nrf2 to exert potent anti‐oxidant effects (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Under various internal and external conditions, the enhanced expression of SIRT1 in mesenchymal stem cells promotes osteogenic differentiation 17 and protects against bone loss 18 . Correspondingly, the downregulation of SIRT1 promotes osteoclastogenesis and osteolysis in mice 46,47 . To verify whether resveratrol‐mediated analgesic effect through the activation of SIRT1‐triggered osteogenesis in the porous endplates, the SIRT1 OSX −/− mice were employed.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro pharmacological up-regulation and activation of SIRT1 with resveratrol ameliorated the particle-induced osteoblastic apoptosis and inflammatory cytokine expression by suppressing SIRT1-p53 and SIRT1-NF-κB signaling, respectively. Unsurprisingly, in vivo SIRT1 activation by resveratrol and GYY4137 protected cells from osteoblast dysfunction, attenuated particle-induced inflammatory responses, and osteolysis in PIO mouse models (Deng et al, 2017b;Liu et al, 2020).…”
Section: Pharmacological Targeting Of Osteoblasts To Limit Periprosthmentioning
confidence: 99%